The Legal Appraisal of the Nature of Liability of Land Transport Operators in Cases of Accidents in Cameroon - Kombo, Kutiefe Umaro (International Multilingual Journal of Science and Technology, 2026)
Land transport operators in Cameroon can be criminally and civilly liable as a result of an accident resulting from their actions. This is provided for in section 289(1) of the penal code1. The criminal liability can be either in tort law, like in negligence, vicarious liability and strict liability, as well as under contract law. The criminal liability can be for an imprisonment term, the payment of a fine, or loss of life or destruction of property. However, the nature of liability in cases of accidents is faced with problems in Cameroon, as the cases suffer from continuous delay before the courts, weak sanctions provided in the penal code and more. This paper sets out to examine the efficiency of the nature of liability of transport operators in cases of accidents in Cameroon. A doctrinal research method has been adopted where the researcher has analyzed both primary and secondary sources of information. The primary sources are the laws and cases decided by courts, while the secondary sources are other write up which the researcher consulted to complete the research paper. Our findings reveal that the laxity of the courts and weak sanctions provided by the Penal code affects the effectiveness of the liability regime for transport operators in cases of accidents. We recommend that the penal code be revised and a more stringent criminal sanction be put in place. Also, a separate court system should be set up for disputes related to accidents to solve the problem of continuous delay before the courts.
Keywords: Accidents; Land Transport Operators; Nature of Liability; Responsabilité; Transport par route; Transporteur

The Effectiveness of the Legal Frameworks in the establishment of Liability of Land Transport Operators in cases of Accidents in Cameroon: A Critical Appraisal - Kombo, Kutiefe Umaro (International Multilingual Journal of Science and Technology, 2025)
The liability of land transport operators in Cameroon is guaranteed by a good number of laws including; the constitution of Cameroon, the penal code, the 2001 law governing the Profession of Road Transport Operators, the 2023 law governing the rail sector in Cameroon and more. Such liability can be under the Tort of negligence, vicarious liability, or strict liability as provided for under section 289(1) of the Cameroonian penal code on Unintentional killing. However, the laxity of the courts in handling accident-related disputes, the contradictory and vague nature of the laws on the liability regime and even the lenient nature of the sanctions provided for by these laws do not meet up with the rate of accidents today in Cameroon. This article therefore has as its objective to examine the effectiveness of the legal frameworks in the establishment of liability of land transport operators in cases of accidents in Cameroon. Arguably, the author holds that the legal frameworks establishing the liability of land transport operators in cases of an accident in Cameroon are ineffective. A doctrinal research method has been adopted where both primary and secondary sources of information have been consulted. Our finding reveals that; the ineffectiveness of legal frameworks in the establishment of the liability of land transport operators in cases of accidents is a result of the laxity of the courts in implementing the laws and, the vague and contradictor nature of the law. We, therefore, recommend that; separate court hearings should be set for accident-related disputes and judges trained only on that, the laws should be revised, the sanctions in cases of accidents should be increased and all mitigating circumstances in cases of accidents should not be taken into consideration like a first-time offender, the plea of guilt etc.
Keywords: Accidents; Cameroun; Land Transport Operators; Liability; Opérateurs de transport terrestre; Responsabilité; Transport terrestre

The Rotterdam Rules Convention: United Nations Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea 2008 - Laurijssen, Peter (CMI, 2024)
Keywords: MARITIME LAW; UN Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea (2008)

Chapter 11, First principles in transportation law and policy - Levine, Jonathan; Shill, Gregory H. (A Research Agenda for US Land Use and Planning Law, 2023)
The main purpose of transportation is connecting people to destinations they value. This seemingly banal statement would, if taken seriously in policymaking, upend transportation and land use planning. Today, planning agencies rely on key performance indicators (KPIs) to measure outcomes. While ostensibly neutral and technical, these measurements in fact imply policy judgments and drive legal consequences. They operate both as a shield against litigation and as a sword to justify new projects. But the way KPIs are set up reflects confusion about basic purposes. They are used to plan and evaluate based not on the ability to reach anything but rather simply to accelerate the speed of traveling. We seek to anchor transportation policy discussion in first principles. The shift we propose is mode agnostic in that it is relevant to all means of transportation. Even so, shifting from a goal of speed to one of reachability would be a leap. We believe such a shift suggests important open questions regarding the barriers to reform and we engage a few of them.

Legal scope of the carrier's liability in the contract of carriage of goods by sea - Drici, Amina (Journal OF LEGAL STUDIES, 2023)
The area of responsibility of the sea freight carrier is to determine the scope of liability over time for damage to the goods and is reflected in the search for the beginning and end of its liability; as well as the determination of the damage which triggers the carrier's obligation to compensate for the losses, damage, delay and determine the persons responsible for the damages for which the recipient or beneficiary of the goods has the right to recourse.
Keywords: Liability; Material scope; Personal scope; Sea carrier; Time scope; Transportation of goods

Determining the Liability for Carriage of Goods by Road in West Africa - Can OHADA Uniform Rules on Transport be a Foundation? - Osinuga, Damilola (Southern African Journal of Policy and Development, 2022)

The legal framework for multimodal transport in West Africa: the African Continental Free Trade Area in perspective - Osinuga, Damilola (World Maritime University, 2022)
This thesis examines how multimodal transport can play a role in achieving the objectives of the African Continental Free Trade Area (AfCFTA). The thesis argues that multimodal transport is cheaper compared with unimodal transportation. While there are a number of issues affecting the operationalisation of multimodal transport in Africa, this study considers, at its core, the legal regimes and other fragmented institutional and governance frameworks of multimodal transport in West Africa. The fragmentation of the legal framework governing multimodal transport leads to uncertainty and unforeseeability of the liability of parties involved in multimodal transport, consequently leading to increased legal costs. There is an undisputed view that for effective regional integration, which Africa is seeking to achieve through the establishment of the African Continental Free Trade Area, there is a need to eliminate all trade barriers. Trade barriers (tariff or non-tariff barriers) should be removed to improve competitiveness and reduce trade friction costs. In other words, to achieve the objectives of the African Continental Free Trade Area, it is essential that all unnecessary costs associated with trade are eliminated or reduced to the barest minimum. The process of doing this is called trade facilitation. This thesis looks at the impact of trade facilitation on regional integration and trade. This thesis’ original contribution to knowledge is that Africa’s regional integration process needs cost-effective transportation in order to achieve smooth market access, and multimodal transportation can provide the most cost-effective solution. However, the legal uncertainty and complexities that could potentially ensue from the use of multimodal transport make it unattractive to prospective users. Accordingly, actions must be taken to reduce legal ambiguity and create a system in which liability is foreseeable and predictable. This study reveals that the current legal framework is incomplete, unsatisfactory and, ultimately, leads to uncertainty. The thesis further contends that neither the option of freedom of contract nor improving the current system of various Economic Community of West African States (ECOWAS )member-states’ view of multimodal transport, can significantly improve the current fragmented system or deliver the needed certainty. Accordingly, the thesis proposes that a modified uniform system would help achieve the legal certainty needed for multimodal transport. The thesis finally submits that the ECOWAS should establish a legally binding, regional governance regime on multimodal transport and a majority of its member-states should ratify the instrument.

The impact of the pandemic on the legal regulation of entrepreneurial activity of transport companies - Rubtsova, Natalya (Transportation Research Procedia, 2022)
The purpose of this paper is to analyze the trends of legal regulation in the business activity under the conditions of new coronavirus infection. The dialectical method of research in conjunction with a retrospective and comparative analysis made it possible to identify three main trends in the legal regulation of entrepreneurial activity in the framework of new socio-economic realities. The increasing role of state regulation of entrepreneurial activity, based on the use of public and legal means, due to the need to increase state intervention in the activities of entrepreneurs is shown. The state support of business for the subsequent development of the economy and compliance with the social balance is also increasing. Accordingly, the social importance of entrepreneurial activity is growing. The pandemic has also intensified the digitalization of entrepreneurial activity, of transport companies, since many traditional forms of doing business are limited by the forced isolation of society. Individual means of digitalization, including the industrial Internet of Things, e-commerce, and smart contracts, have become most prevalent. Consequently, the pandemic cannot be viewed only as a negative factor, its impact on entrepreneurial activity also has a positive effect.
Keywords: Business; axiology; digitalization; means of legal regulation; pandemic; transport companies

Airport Charges Regulation: A Private Law Approach - Mei, Di (McGill University, 2022)
This thesis explores the regulation of airport charges, which is an important but marginalised topic. It particularly examines how private law instruments can play a role in the regulatory process. Airports used to be subject to traditional regulation, which operates in a command-and-control mode. As the airport industry becomes increasingly complicated, traditional regulation seems problematic. First, the method that is associated with traditional regulation to draw a line between regulated and unregulated airports has downsides. Second, the international regulatory framework on airport charges lacks binding rules. This suggests that traditional regulation is not the best niche for airport charges regulation. Third, good regulation needs independent regulatory bodies, which are hard to achieve in practice.In this context, this thesis argues that a private law approach can serve as a more flexible and effective way to regulate airport charges. There are two instruments under this overarching approach. First, contracts can be adopted to incorporate airport charges regulations. Second, robust corporate governance generates the effect of good regulation. This is an interdisciplinary work that has engaged air law, contract law, corporate law, competition law, and aviation business and management. It also employs the method of case studies. Chapter 4 examines the regulation of airport charges in the UK, Canada, and India. The three case studies demonstrate that private law instruments have been implicitly implemented to different degrees in these countries. These demonstrate the feasibility of applying private ordering in the regulatory process. I also look into the regulation of countries and regions including Australia, Ireland, the EU, and Germany throughout this thesis. This study also examines a specific sector of airport charges, namely, charges for ground-handling services. This sector possesses a unique feature in that it is between aeronautical and non-aeronautical services. A private law approach can also be adopted in the regulation of charges relating to ground-handling services. Additionally, ICAO as an important international organisation governing international air transport can also contribute to a private law approach of airport charges through its soft-law making function. This thesis aims to shed light on a private law approach, as an innovative regulatory mechanism, to airport charges. That said, regulation by this approach and traditional regulation are not contradictory but can cooperate to an extent, depending on how much power one wants to give to private ordering
Keywords: Airport; Regulation

An Empirical Study of Dispute Resolution Clauses in International Supply Contracts - Coyle, John F.; Drahozal, Christopher R. (Vanderbilt Journal of Transnational Law, 2018)
International transactions present unique legal risks. When a contract touches several different nations, a party may not know where it will be called upon to defend a lawsuit or, alternatively, which nation’s law will be applied to resolve that dispute. To mitigate these risks, parties will often write dispute resolution provisions into their contracts. Arbitration clauses and forum selection clauses help to reduce uncertainty relating to the forum. Choice-of-law clauses help to reduce uncertainty as to the governing law. Over the past few decades, such provisions have become commonplace in international contracting. And yet there exist vanishingly few empirical studies exploring the use of these provisions in international commercial agreements.

Institutional and Contextual Factors Effects on Entrepreneurship in Cameroon: The Case of the Transport Sector - Okah-Efogo, Françoise; Okah-Atenga, Crescence Marie-France (Entrepreneurship in Africa, 2017)
In Africa, whatever the considered age group, there are more entrepreneurs in the early stages of entrepreneurship than anywhere else in the world (Global Entrepreneurship Monitor (GEM) Report 2014). According to the gem survey (2014), 55.57 per cent of the population between 18–64 years expresses entrepreneurial intentions in Cameroon. Similarly, 37.4 per cent of the same age population is in the early course of their business activity. Between 2014 and 2015, total entrepreneurial activity has decreased in Cameroon (from 37.4 per cent to 25.4 per cent of all adults). Nonetheless, 61.1 per cent of the respondents think that entrepreneurship

Remedies for passengers for flight delays caused by force majeure - Ko, Li-Juan (McGill University, 2016)
This thesis intends to justify the necessity to propose an alternative remedy mechanism to current air carriers' obligations in offering complimentary services to passengers in force majeure delays. This mechanism mitigates disputes arising from passengers' dissatisfaction with air carriers' services. The proposal is the result of extensive research arising from a fundamental question: Who should be responsible for damages and/or inconvenience resulting from flight delays caused by force majeure? The source of information for this thesis stems from a combination of the analysis of case law and statutes on one hand, and experience drawn from professional practice and cultural context on the other. This thesis discusses the intersection of international conventions, national legislation, and the practice and expectations of air carriers and their passengers. The thesis specifically examines and highlights the inadequacies of relying on existing international conventions to provide a harmonized solution for flight delay claims. In terms of national remedy mechanisms, research and analysis have been focused on the advanced aviation markets in the West, such as the US and the EU, and on the emerging markets in the East, such as Mainland China and Taiwan. The research and analyses reveal how national laws, which are deeply influenced by socio-economic, political and cultural factors, trigger distinct conflicts of interest between air carriers and passengers. During the course of reviewing the legal jigsaw and uncertainties in current legal practice, the findings revealed more issues. In brief, making more laws cannot guarantee an effective solution for flight delay claims, especially in different jurisdictions. Accordingly, the findings support that a novel solution, free from the uncertainties and complexities in the current legal framework, is needed to resolve passengers' claims or expectations resulting from force majeure delays. Essentially, this novel solution is to form an alternative remedy mechanism that includes a fund and codes of conduct. The fund will implement a risk-sharing function among stakeholders that will include passengers, air carriers and airport managing entities. To mitigate disputes, the proposed codes of conduct will include guidelines to operate the fund with the aim of mutual respect between passengers and air carriers. In so doing, the remedy mechanism will provide equitable answers to the question: "Who should be responsible for damages and/or inconvenience resulting from flight delays caused by force majeure?"
Keywords: Air carriers' obligation; Alternative remedy; Flight delay; Force majeure; Remedies

A level playing field for "open skies": the need for consistent and harmonized regulation of Aviation - Fitzgerald, P. Paul (McGill University, 2015)
Various initiatives by regulators in different jurisdictions over the past two decades have completely reshaped the airline industry in ways that were unimaginable in 1992. From an industry dominated by Pan Am and Trans World Airlines (TWA), and newly privatized airlines such as British Airways, today's industry is dominated by government-owned intercontinental airlines based in the Middle East and carrying passengers the majority of whom are ultimately destined for States other than the States where the airlines are based. Insufficient thought has been given to whether this evolution is desirable, whether it involves profound competitive distortions or whether it is in the public interest that the majority of Australians visiting Europe are carried by an airline based in neither jurisdiction or that a similar claim might be made with respect to traffic between South Asia and the Americas. This thesis examines the events that have reshaped the international aviation industry over the two decades between 1992 and 2012. It will critically analyze the major developments and the regulatory responses and highlight some of the incompatible and disjointed regulations that are in effect at either end of international routes. It ultimately proposes that Australia, Canada, the European Union (EU), New Zealand and the United States (US) form a small international organization, to be known as the Open Skies International Aviation Block (OSIAB). OSIAB would be based on expanding the membership of the US-EU Joint Committee foreseen in the 2007 US-EU Open Skies Agreement and expanding its scope to cover every aspect of the regulation of international commercial aviation. This thesis argues such a forum is necessary to ensure that regulations in different countries are aligned so that competitive distortions potentially caused by regulatory disharmony are minimized, thus allowing the international airline industry to compete on the level international playing field that so many international agreements have promised to create.
Keywords: Aviation; Aviation regulation; Transport aérien

The impact of non-operationalisation of the SADC protocol and international transport agreements on cross border road transport movement in the SADC region - Monyepao, Kaine (34th Annual Southern African Transport Conference 6-9 July 2015, 2015)
The failure by Sothern African Development Community (SADC) countries to fully implement the SADC Protocol on Transport, Communications and Meteorology (the Protocol) and bilateral agreements in regard to road transport negatively impacts the seamless movement of cross border road transport and significantly contributes to the challenges faced by the cross border industry as a whole. The full implementation of the Protocol in regard to road transport, and bilateral agreements would lead to efficient cross border transport regulation and transportation and in turn culminate in reduction of challenges facing the sector. This would lead to reduction of transportation costs, improvement in productivity, and accelerated growth in intra-regional trade, regional economic integration and overall SADC socio-economic development. This paper outlines the extent to which the provisions of the Protocol and bilateral agreements have been implemented by SADC countries and the key challenges emanating from the partial operationalisation of the instruments. The paper is based on findings from engagements with key government and private sector stakeholders in the regional transport environment and various research conducted by the C-BRTA between 2011 and 2014. The partial operationalisation of the instruments has resulted in disjointed regulatory frameworks and inability to: holistically address corridor constraints/ non-tariff barriers, facilitate seamless cross border movements, facilitate liberalisation of access to transport markets in the region, harmonise standards and procedures, and facilitate economic growth and trade between SADC countries. It is possible for the SADC region to realise the aspirations set out in the Protocol and bilateral agreements, and this paper outlines some of the solutions. To begin with, there is need for SADC countries to embrace the need to eradicate the existing self-centric regulatory approach limited to micro-needs and market protectionism. This would need to be underpinned by strong orientation towards the need to achieve macro benefits emanating from a regional perspective in regard to regulating cross border road transport movement. Taking off from this departure point, SADC countries can objectively establish a solid ground towards fully operationalising the Protocol and bilateral agreements. This paper outlines some of the interventions that can be implemented to ensure SADC countries fully operationalise the provisions of the Protocol on transport and bilateral agreements.
Keywords: Southern African Transport Conference; Transportation

Airline labour law : a study of certain labour law rules in international air transport - Huang, Chu Cheng (McGill University, 1997)
This thesis examines problems related to particular labor laws currently applied in international air transport. This analysis is framed within the context of scholarly theory and judicial practice arising from various regimes of labor law governing industrial injury, the individual contract of employment, labor-management relations, and fair treatment in the civil aviation industry. A critical survey of labor regulations operating in the international air transport industry is provided through commentary on the principles formulated by judicial decisions and the theories which underlie their reasoning, helping to clarify both substantive and procedural labor laws affecting international air transport. A critical analysis of different categories of statutory labor law governing international air transport is also provided to assess the validity of commonly-erected conflict of labor law rules, thereby revealing the inadequacy of the single rule principle in view of the unique and perplexing regulatory interests which are inherent in aviation activity. The divergence between domestic labor statutes and Treaties of Friendship, Commerce and Navigation or bilateral air transport agreements also adds a more subtle aspect to the problems explored.
Keywords: Air transport; Airline; Droit du travail; Labour law; Labour relations; Transportation

Africa’s Civil Aviation Law and Policy - Ndum, Fidelis Nkom (McGill University, 1984)
The sources of Africa's Civil Aviation Law and Policy are various. The region's political economy as well as its historic relationship with Europe have significant influences on its civil aviation law and policy which, nevertheless, cannot deviate from the international legal framework (Chapters 1-3). […] Le droit et la politique de l'aviation civile africaine ont des sources variées. L'économie politique de la région ainsi que ses relations historiques avec l'Europe influencent de façon importante le droit et la politique de 1 'aviation civile africaine qui' néanmoins, ne peut s'écarter de la structure juridique internationale (chapitres 1-3). […]
Keywords: Civil aviation (Law); Civil aviation (Policy); Commercial Aeronautics; Government policy; Transport aérien

The regional integration of commercial air transport in Africa : political, economic and legal considerations - Kaunda, Gideon H. (McGill University, 1983)
The introduction of this dissertation discusses geopolitical and socio-economic factors which influence transportation in Africa. Chapters II and III, respectively, analyse the concept of regionalism and the legal framework of multinational civil aviation co-operation. The economic advantages of surface and air transportation are compared in Chapter IV. Chapter V is a general survey of the impact of nationalism on socio-economic co-operation. To illustrate the extent of political problems, in economic and aeronautical co-operation, the former East African Community is reviewed in Chapter VI. The demised East African regional carrier is specifically discussed in Chapter VII. Chapter VIII highlights the notion in functionalism as an approach to the attainment of socio-economic integration. Multilateral organizations responsible for co-ordinating and fostering co-operation are examined in Chapters IX, X and XI. Current regional activities and future prospects are essessed in the penultimate chapter. The conclusion contains the essential elements required in creating regional airlines in Africa.
Keywords: Africa; Air transport; Commercial air transport; Regional integration

Legal regulation of civil aviation in Commonwealth Africa : a comparative study - Odubayo, Wilberforce Oladele (McGill University, 1973)
In this comparative study, we examine the legal regulation of civil aviation in Commonwealth Africa. In Chapter 1, we examine the history of Nigeria, Ghana, Kenya, Uganda, Tanzania and the evolution of the East African Community. Chapter 2 deals with colonial regulation of aviation. In Chapter 3, we consider problems of state succession in relation to aviation during the periods of transition to independence. Chapter 4 deals with treaty-making procedures of the respective states, while in Chapter 5, we examine the legislative, administrative and judicial processes of these states in relation to aviation. Licensing of air transport undertakings is considered in Chapter 6, while Chapter 7 is devoted to designation and control of airports. Some aspects of international economic law concerning aviation are considered in Chapter 8, while in Chapter 9, we examine the reconstruction of the state-owned airlines. In Chapter 10, we summarize and draw final conclusions. REGLEMENTATION LEGALE DE L'AVIATION CIVILE EN AFRIQUE DU COMMONWEALTH: UNE ETUDE COMPARATIVE Dans la présente étude comparative, nous examinons la réglementation légale de l'aviation civile en Afrique du Commonwealth. Dans le premier chapitre, nous examinons l'histoire du Nigéria, du Ghana, du Kenya, de l'Ouganda, de la Tanzanie et l'évolution de la Communauté est-africaine. Le chapitre 2 traite de la réglementation coloniale de l'aviation. Dans le chapitre 3, nous considérons les problèmes de la succession d'Etats en rapport avec l'aviation pendant les périodes de transition vers l'indépendance. Le chapitre 4 traite des procédures d'élaboration des traités des différents Etats, tandis que dans le chapitre 5, nous examinons les procédures législatives, administratives et judiciaires de ces Etats en ce qui concerne l'aviation. La réglementation des permis des entreprises de transport aérien est passée en revue dans le chapitre 6 alors que le chapitre 7 est consacré aux conditions de création et de fonctionnement et au contrôle des aérodromes. Certains aspects du droit économique international particuliers à l'aviation sont évoqués dans le chapitre 8 et dans le chapitre 9, nous examinons la reconstruction des lignes aériennes possédées par l'Etat. Finalement, dans le chapitre 10, nous donnons un résumé et tirons les conclusions générales
Keywords: Civil aviation (regulation); Commercial Aeronautics; Commonwealth; Transport aérien